Cardiovascular profiles associated with white matter hyperintensities in healthy young women - McBride, Carole A.; Russom, Zane; Achenbach, Ella; Bernstein, Ira M.; Dumas, Julie A. (Frontiers in Physiology, 2023)
Women who experience hypertension in pregnancy have increased risk of both chronic hypertension and dementia. High blood pressure is associated with increased evidence of white matter hyperintensities (WMH) in brain imaging. WMH are disruptions of the white matter of the brain that occur with demyelination and axonal degeneration, are associated with vascular disease, occur more frequently in people with hypertension, and are associated with cognitive impairment. We evaluated the relationship between WMH and subclinical cardiovascular function in healthy young nulliparous women and women with a history of early-onset preeclampsia. Sixty-two reproductive-aged women were assessed during the follicular phase of the menstrual cycle after a 3-day sodium/potassium-controlled diet. Half of participants had a history of early-onset preeclampsia, and half were nulliparous. Blood was drawn to assess inflammatory markers. Cardiovascular assessments included tonometric blood pressure monitoring, volume loading to assess vascular compliance, echocardiography to assess cardiac ejection time, brachial pulse wave velocity of the brachial artery, assessing cardiovascular stiffness, and brachial artery flow mediated vasodilation to assess endothelial mediated dilatory response. T2 fluid-attenuated inversion recovery (FLAIR) MRI imaging was obtained. Two raters, blinded to cardiovascular assessments and pregnancy history, reviewed MRI scans for evidence of WMH using the Fazekas rating scale. WMHs were detected in 17 women; 45 had normal white matter structure. Participants with Fazekas score>0 had exaggerated response to volume loading compared to women with a Fazekas score of 0 and longer cardiac ejection times. Fazekas scores > 0 had lower brachial flow-mediated vasodilation and increased white blood count compared to those with no evidence of WMH. Women with WMH had reduced cardiovascular compliance, and a trend towards decreased endothelial responsiveness compared to those without WMH. These data demonstrated that the relationship between cardiovascular and brain health was detectable in young, healthy, reproductive-aged women, and may play a role in later development of clinical disease. These findings may help identify women who are at risk for cognitive decline and pathological aging.